Cimahi Pay as a Digital Payment Solution for MSMEs in Indonesia - sudrajat, jajat; Syamil, Ahmad; Rangkuti, Abdul Haris; Utomo, Satrio Matin; Sardjono, Wahyu; Syafaat, Raden Raka Abduk Kamal (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2025)
In today's digital age, a territorial payment system is essential to drive local economic progress. Cimahi, as the economic center of West Java, has a great opportunity to develop more open and inclusive payment methods today. However, many people, both those who live there and those who have just arrived, experience limitations in accessing transactions digitally. Most transactions in MSMEs are still done in cash, which hinders the growth of small businesses and limits payment flexibility. The research method in this study uses a qualitative method of a case study approach, through a literature review of digital information media information data. Case study research is carried out to gain a deeper understanding of a condition and the meaning of an object that is the object of research. Case studies are analyzed from the results of business start-ups. The results of the study show that users can save balances, make digital payments at local merchants, transact more efficiently and profitably, and have wide cooperation potential. This platform allows companies and local governments to work together to encourage local economic growth, thus becoming a prototype for the development of local MSMEs. Keywords: smart city, digital payments, MSME ecosystem